ABS composite material, its preparation method and application

CN121673720BActive Publication Date: 2026-10-20KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511912618.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-10-20
Estimated Expiration
2045-12-18

AI Technical Summary

Technical Problem

[0002]ABS(丙烯腈-丁二烯-苯乙烯共聚物)材料具有良好的加工性能和稳定性,被广泛应用于家用电器如空调、洗衣机等的外壳制件中,然而,由于ABS材料在常温下为玻璃态,质地较硬,因此材料在局部受热(例如因搬运发生摩擦产热,或者家电长时间使用,电机发热,使得材料的温度提升至60~70℃的较高温时),材料相互摩擦时会出现“粘滑现象”,也即材料的静摩擦和滑动摩擦交替出现,进行出现高频异响

Benefits of technology

[0045]优选地,所述外壳制件为家电外壳制件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses an ABS composite material and a preparation method and application thereof, and belongs to the technical field of high polymer materials. The ABS composite material is prepared by compounding high glue powder and crystalline resin in SAN resin, and introducing organic thermal expansion microspheres and superfine inorganic particles as functional fillers. The ABS composite material can effectively solve the abnormal sound defects of the ABS material product in use, and does not affect the appearance effect and mechanical effect after processing, and has excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to an ABS composite material, its preparation method, and its application. Background Technology

[0002] ABS (acrylonitrile-butadiene-styrene copolymer) material has good processing performance and stability, and is widely used in the outer shell of household appliances such as air conditioners and washing machines. However, because ABS material is in a glassy state at room temperature and is relatively hard, when the material is locally heated (for example, due to frictional heat generated during handling, or when the temperature of the material rises to a relatively high temperature of 60~70℃ due to prolonged use of household appliances), a "stick-slip phenomenon" will occur when the materials rub against each other. That is, static friction and sliding friction of the materials alternate, resulting in high-frequency abnormal noise.

[0003] To solve the problem of abnormal noise, people have tried to modify the resin matrix of ABS material to adjust the state of the material at room temperature. However, this approach may lead to other defects in the material, such as poor appearance or a significant reduction in the mechanical strength of the material, making it unsightly or easily damaged when used in casings. Summary of the Invention

[0004] Based on the shortcomings of existing technologies, the purpose of this invention is to provide an ABS composite material. By compounding high-rubber powder and crystalline resin in SAN resin, and introducing organic thermal expansion microspheres and ultrafine inorganic particles as functional fillers, it can not only effectively solve the abnormal noise defects that may occur in ABS material products during use, but also does not affect the appearance and mechanical properties after processing, resulting in excellent comprehensive performance.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: An ABS composite material comprising the following components in parts by weight: 50-70 parts of SAN resin, 20-30 parts of high-colloidal powder, 20-40 parts of crystalline resin, and 5-15 parts of functional filler; The functional filler includes thermally expandable microspheres and ultrafine inorganic particles; The average particle size of the organic thermally expandable microspheres is ≤35μm; The retained particle size D of the ultrafine inorganic particles v50 ≤1.5μm.

[0006] To address the issue of rattling noise caused by the sticky, slippery properties of existing ABS materials when used in appliance casings, this invention uses SAN resin (styrene-acrylonitrile copolymer) as the matrix, incorporating high-adhesion powder and crystalline resin in a compound. This transforms the overall resin composition from its original glassy state to a unique glassy-viscoelastic state at higher temperatures (e.g., around 60-70°C). In this state, even if localized friction occurs, the increased sound absorption reduces sound transmission, thus minimizing rattling. Furthermore, compared to traditional ABS materials which rely on inorganic materials (e.g.,...), this approach... Using fillers such as glass fiber and large-particle talc, the ABS composite material of this invention uses two functional materials as composite fillers: organic thermally expandable microspheres and ultrafine inorganic particles. The organic thermally expandable microspheres expand upon heating, creating cavities in the overall product, further absorbing sound from within. The ultrafine inorganic particles fill the surface of the thermally expandable microspheres and the organic composite resin matrix, extending the sound wave propagation path and causing sound dissipation. Through the synergistic effect of the resin, thermally expandable microspheres, and ultrafine inorganic particles, the frequency of abnormal noise in the product is significantly reduced. Furthermore, by limiting the size of the thermally expandable microspheres and the ultrafine inorganic particles, the mechanical strength of the product can be avoided after the thermally expandable microspheres expand and create cavities. The product has a high flexural modulus, and these materials do not exhibit compatibility or dispersibility issues, so the appearance is largely unaffected. If either of these two functional fillers is missing, the product's noise reduction effect will not meet expectations. If the size of either is too large, it will not only affect the material's sound absorption and dissipation effect, but may also weaken the product's mechanical strength due to uneven dispersion or even local agglomeration, and may even cause precipitation, resulting in poor product appearance.

[0007] Preferably, in the ABS composite material, the weight parts of SAN resin are 50 parts, 52 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, and 70 parts, or any two of these; the weight parts of high-polymer powder are 20 parts, 22 parts, 25 parts, 28 parts, and 30 parts, or any two of these; the weight parts of crystalline resin are 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, and 40 parts, or any two of these; and the weight parts of functional filler are 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, and 15 parts, or any two of these.

[0008] More preferably, the ABS composite material comprises the following components in parts by weight: 50-70 parts of SAN resin, 22-27 parts of high-polymer powder, 25-38 parts of crystalline resin, and 6-15 parts of functional filler.

[0009] More preferably, the SAN resin has a mass content of ≥40wt% in the ABS composite material.

[0010] In the technical solution of the present invention, the product can achieve sufficient flexural modulus when the proportion of matrix resin is relatively high. On this basis, those skilled in the art can further adjust the proportion of the product components according to actual needs, without making any special limitations.

[0011] Preferably, the acrylonitrile content of the SAN resin is 20-30% by mass, and the melt flow rate at 220°C and 10kg load according to ISO1133-2011 is 5-50g / 10min, more preferably 10-40g / 10min.

[0012] It should be noted that the acrylonitrile content of the SAN resin described in this invention can be determined using an infrared quantitative method. The infrared spectrum obtained from testing a known standard sample containing benzene rings and acrylonitrile groups is then analyzed at 1600 cm⁻¹. -1 The characteristic peak of the benzene ring at 2237 cm⁻¹ -1 The intensity ratio K of the two acrylonitrile characteristic peaks is calculated. Then, a calibration curve of acrylonitrile content versus K is established. Finally, the acrylonitrile content is compared with the K obtained from the test of the product.

[0013] More preferably, the SAN resin is a styrene-acrylonitrile random copolymer prepared by emulsion polymerization.

[0014] Preferably, the high-adhesion powder is polybutadiene high-adhesion powder; More preferably, the butadiene monomer content in the high-polymer powder is 55-65%.

[0015] Preferably, the crystalline resin includes at least one of PET (polyethylene terephthalate), PBT (polybutylene terephthalate), PCTG (polyethylene glycol-1,4-cyclohexanediol terephthalate), and PETG (polyethylene glycol-1,4-cyclohexanediol terephthalate).

[0016] The type of crystalline resin in the ABS composite material described in this invention is not specifically limited. As long as the resin in the product can form a glassy-viscoelastic state at a higher temperature and does not affect the noise reduction, appearance, and mechanical strength of the product, it is acceptable.

[0017] In some embodiments, the crystallization degree of the crystalline resin, as tested according to ASTM D3418-2021, is 30-60%.

[0018] More preferably, the melting temperature Tm of the crystalline resin is 230℃≤Tm≤250℃.

[0019] Preferably, the organic thermally expandable microspheres include a shell and a core, the shell comprising an acrylic resin and the core comprising expandable alkane.

[0020] More preferably, the expandable alkane includes at least one of isobutane, isooctane, pentane, and isopentane.

[0021] More preferably, the mass content of expandable alkanes in the organic thermally expandable microspheres is 5~40wt%.

[0022] Preferably, the average particle size of the organic thermally expandable microspheres is 2~25μm, and the initial expansion temperature is ≥85℃.

[0023] More preferably, the average particle size of the organic thermally expandable microspheres is 5~25μm, and the initial expansion temperature is 85~110℃.

[0024] More preferably, the average particle size of the organic thermally expandable microspheres is 5~25μm, and the initial expansion temperature is 85~95℃.

[0025] It should be noted that the initial expansion temperature of the organic thermally expandable microspheres refers to the initial temperature at which the material begins to expand after heating. Specifically, this can be tested using a TMA Q-400 thermomechanical analyzer. A 1mg sample is placed in the detector and sealed. The temperature is increased to 280℃ at a rate of 20℃ / min. A force of 0.1N is applied to the probe, and the vertical displacement of the probe is analyzed. The temperature at which the probe begins to move is recorded as the initial expansion temperature. The average particle size of the organic thermally expandable microspheres is directly confirmed using a two-dimensional microscope. At a magnification of 50-500x, the material is positioned and magnified under the microscope to 300-800x. At a fixed magnification, at least 100 organic thermally expandable microsphere particles within the same plane are screened using mapping software for particle size testing, and the average value is calculated. This average particle size is the final average particle size.

[0026] Preferably, the maximum expansion temperature of the organic thermal expansion microspheres is 135~190℃.

[0027] It should be noted that the maximum expansion temperature of the organic thermal expansion microspheres described in this invention refers to the temperature at which the probe no longer undergoes vertical displacement after the test temperature exceeds the initial expansion temperature when the TMA Q-400 thermomechanical analyzer is used for detection. In other words, the temperature is the critical expansion temperature of the organic thermal expansion microspheres. Once the temperature is exceeded, the organic thermal expansion microspheres will no longer expand.

[0028] The degree of expansion of organic thermal expansion microspheres varies with their initial expansion temperature. At the same time, when the particle size is different, the size of the cavity formed and the dispersion effect in the product also vary. When the initial expansion temperature and average particle size of the organic thermal expansion microspheres are preferably within the above range, not only can the sound absorption effect of the product be further improved, but the component dispersion is also better and the flexural modulus is higher.

[0029] Preferably, the ultrafine inorganic particles include at least one of ultrafine talc, ultrafine alumina, ultrafine magnesium oxide, ultrafine silicon dioxide, and ultrafine titanium dioxide.

[0030] More preferably, the retained particle size D of the ultrafine inorganic particles v50 The thickness is 0.5~1.5μm.

[0031] It should be noted that the retained particle size D of the ultrafine inorganic particles described in this invention... v50 The following method can be used for confirmation: ABS composite material is placed in a muffle furnace and pyrolyzed at 500°C. The resulting ash is dispersed with ethanol and then tested using sedimentation analysis method according to ISO 13317-4:2014.

[0032] The specific type of ultrafine inorganic particles described in this invention is not limited. Any inorganic filler commonly used in organic plastics by those skilled in the art is acceptable. Compared with organic fillers, inorganic particles have better chemical stability and dimensional stability under thermal conditions, which is more conducive to ensuring the mechanical strength level of the overall product after the introduction of organic thermal expansion microspheres.

[0033] Preferably, in the functional filler, the mass ratio of organic thermally expandable microspheres to ultrafine inorganic particles is 1:(0.2~17).

[0034] More preferably, the mass ratio of organic thermally expandable microspheres to ultrafine inorganic particles is one or any two of the following: 1:0.2, 1:1, 1:2, 1:5, 1:8, 1:10, 1:12, 1:15, 1:17.

[0035] More preferably, the mass ratio of the organic thermally expandable microspheres to the ultrafine inorganic particles is 1:(2~8).

[0036] As described above, the product of the present invention can achieve the effect of preventing abnormal noise. In addition to the selection of the matrix resin compound, the compounding of functional fillers is also a necessary key factor. After the two are compounded, the sound absorption channels can be increased. When the two are further optimized in the above ratio, the sound absorption effect of the product is better and the performance of preventing abnormal noise is better.

[0037] Preferably, the ABS composite material also includes an antioxidant.

[0038] More preferably, the antioxidant is present in a weight ratio of 0.3 to 1 part.

[0039] More preferably, the antioxidant includes at least one of hindered phenolic antioxidants, phosphite antioxidants, and hindered amine antioxidants.

[0040] When the ABS composite material described in this invention is used in applications such as appliance housings, those skilled in the art can further introduce antioxidants, such as hindered phenolic antioxidants, according to the actual needs of the protected components. Without affecting the product's anti-noise, mechanical strength, and appearance, those skilled in the art can also use other types of antioxidants to impart environmental resistance to the product, which is not limited here.

[0041] Preferably, the components of the ABS composite material may include, but are not limited to, antibacterial agents, lubricants, etc. Based on the processing or actual use needs of those skilled in the art, other types of functional additives may be added without affecting the expected performance of the product. For example, the above-mentioned additives can improve the antibacterial ability and demolding success rate of the product without affecting the characteristic performance of the product. That is, the description of the product components in the technical solution of the present invention is not a limitation on the types of components.

[0042] Another object of the present invention is to provide a method for preparing the ABS composite material, comprising the following steps: The components are added to a screw extruder for melt extrusion and granulation to obtain the ABS composite material.

[0043] Preferably, the temperature zones of the screw extruder are set as follows: Zone 1 220~230℃, Zone 2 220~230℃, Zone 3 230~240℃, Zone 4 230~240℃, Zone 5 230~240℃, Zone 6 240~260℃, Zone 7 240~260℃, Zone 8 240~260℃, Zone 9 240~260℃, Zone 10 240~260℃, and the screw speed is 350~600 rpm.

[0044] Another object of the present invention is to provide the application of the ABS composite material in the manufacture of housing parts.

[0045] Preferably, the outer casing is a household appliance casing.

[0046] Another object of the present invention is to provide a housing component comprising the ABS composite material described herein.

[0047] The ABS composite material described in this invention, based on the combination of components, when applied to components such as the outer shell of household appliances, will not cause sticking or slipping due to localized high temperatures caused by external friction or heat, thus preventing abnormal noise. The product has excellent sound absorption effect. At the same time, the product can maintain a high flexural modulus level, has good ability to withstand external stress, and will not have poor appearance due to component modification. The overall performance is excellent.

[0048] The beneficial effects of this invention are that it provides an ABS composite material. By compounding high-rubber powder and crystalline resin in SAN resin, and introducing organic thermal expansion microspheres and ultrafine inorganic particles as functional fillers, it can not only effectively solve the abnormal noise defects that may occur in ABS material products during use, but also does not affect the appearance and mechanical properties after processing, resulting in excellent comprehensive performance. Detailed Implementation

[0049] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention. Unless otherwise specified, the experimental reagents and instruments involved in the implementation of this invention are commonly used reagents and instruments.

[0050] Examples 1-11 The ABS composite material of the present invention is described in an embodiment, and the composition of the ABS composite material is shown in Table 1.

[0051] The preparation method of the ABS composite material includes the following steps: The components are added to a screw extruder for melt extrusion and granulation to obtain the ABS composite material.

[0052] Preferably, the temperature zones of the screw extruder are set as follows: Zone 1 220~230℃, Zone 2 220~230℃, Zone 3 230~240℃, Zone 4 230~240℃, Zone 5 230~240℃, Zone 6 240~260℃, Zone 7 240~260℃, Zone 8 240~260℃, Zone 9 240~260℃, Zone 10 240~260℃, and the screw speed is 500 rpm.

[0053] Comparative Examples 1-6 The only difference between each comparative example and Example 1 is the type and ratio of components, as shown in Table 2.

[0054] In the components described in each embodiment and comparative example, The SAN resin 1 is SANKFA-130, produced by Liaoning Kingfa Science & Technology Co., Ltd., with an acrylonitrile content of 26% and a melt flow rate of 40g / 10min at 220℃ and 10kg load. The SAN resin 2 is SAN KFA-180, produced by Liaoning Kingfa Science & Technology Co., Ltd., with an acrylonitrile content of 30% and a melt flow rate of 10g / 10min at 220℃ and 10kg load. The high-rubber powder 1 is HR181, produced by Kumho Chemical, a polybutadiene high-rubber powder with a butadiene content of 58%; The high-rubber powder 2 is EB-168, produced by Shandong Yigong Chemical, a polybutadiene high-rubber powder with a butadiene content of 62%; The crystalline resin 1 is PET BG80, produced by Sinopec Yizheng Chemical Fiber Co., Ltd., PET, with a melting temperature of 245℃. The crystalline resin 2 is PBT GX121, produced by Sinopec Yizheng Chemical Fiber Co., Ltd., PBT, with a melting temperature of 230℃. The organic thermal expansion microsphere 1 is YBL-358, produced by Shandong Yuanbang New Materials, with an average particle size of 10μm and an initial expansion temperature of 90℃. The organic thermal expansion microspheres 2 are YBL-368, produced by Shandong Yuanbang New Materials, with an average particle size of 20μm and an initial expansion temperature of 92℃. The organic thermal expansion microspheres 3 are YBL-558, produced by Shandong Yuanbang New Materials, with an average particle size of 10μm and an initial expansion temperature of 110℃. The organic thermal expansion microspheres 4 are YBL-568, produced by Shandong Yuanbang New Materials, with an average particle size of 20μm and an initial expansion temperature of 110℃. The organic thermal expansion microspheres 5 are YBL-588, produced by Shandong Yuanbang New Materials, with an average particle size of 40μm and an initial expansion temperature of 110℃. The ultrafine inorganic particles 1 are commercially available ultrafine talc powder with an average particle size of 1.3 μm; The ultrafine inorganic particles 2 are commercially available ultrafine silica with an average particle size of 0.65 μm; The inorganic particles 3 are commercially available talc powder with an average particle size of 2.5 μm.

[0055] The inorganic particles 4 are commercially available glass fibers with an average diameter of 13 μm and an average length of 4.5 mm.

[0056] The antioxidant is IRGANOX 1076, manufactured by BASF.

[0057] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment. Table 1 Table 2 To verify the performance of the ABS composite material described in this invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, with the specific steps as follows: (1) Bending modulus test: Each embodiment and comparative example was tested according to standard ISO 178-2019 at a speed of 2 mm / min; (2) Loss factor test: The samples of each embodiment and comparative example were tested according to ISO 6721-1-2011 at a test temperature of 60℃. (3) Decibels test: Each example and comparative example product was injection molded into a 60×60×2mm test square plate. The square plate was then manually rubbed in opposite directions in a quiet room, and a decibel meter was set up in the quiet room to receive the decibel value. (4) Appearance test: For injection molded 150*150*2.5mm square plates, visually inspect the appearance of the square plates under D65 light source to see if there are pits. If there are, the appearance is judged to be defective.

[0058] The test results are shown in Tables 3 and 4.

[0059] Table 3 Table 4 As can be seen from Tables 3 and 4, the ABS composite material of the present invention uses SAN resin, high-rubber powder, and crystalline resin as the matrix resin, and organic thermal expansion microspheres and ultrafine inorganic particles as composite fillers. The organic thermal expansion microspheres expand when heated, creating cavities in the overall product, which further absorbs sound from the inside. The ultrafine inorganic particles fill the surface of the thermal expansion microspheres and the organic composite resin matrix, extending the propagation path of sound waves and causing sound dissipation. Through the synergistic effect of the resin, thermal expansion microspheres, and ultrafine inorganic particles, the frequency of abnormal noise in the product is significantly reduced. In addition, by limiting the size of the thermal expansion microspheres and the ultrafine inorganic particles, the mechanical strength of the product can be avoided after the thermal expansion microspheres expand and create cavities. The product has a high flexural modulus, and these materials do not have compatibility or dispersibility problems. The appearance is basically unaffected. The flexural modulus of the product can reach above 58 MPa, the loss factor is as high as 0.06, and the decibel value is as low as 40 dB or below, with no defects in appearance. In contrast, Comparative Example 1 did not introduce crystalline resin, so it could not overcome the internal friction problem between the matrix resin and the material, resulting in a low loss factor and a high decibel value. Comparative Examples 2 and 3 did not simultaneously use organic thermal expansion microspheres and ultrafine inorganic particles for compounding, so the improvement in the anti-noise effect of the products did not reach the level of the products in the examples. In Comparative Example 4, the size of the organic thermal expansion microspheres was too large. After expansion, the anti-noise effect was improved, but due to dispersibility issues, the improvement was still not up to standard, and it also weakened the mechanical strength of the products. In Comparative Examples 5 and 6, the inorganic particles used were too large, and their dispersibility problem was even more serious, resulting in worse product performance and even pitting and poor appearance.

[0060] As can be seen from Examples 1 and 5-7, when organic thermal expansion microspheres with a lower initial expansion temperature are selected, the expansion occurs earlier, the expansion is more complete, and the uniformity is better, resulting in better noise reduction performance of the product. Furthermore, as can be seen from Examples 1 and 9-11, when the mass ratio of organic thermal expansion microspheres to ultrafine inorganic particles is 1:(2-8), the sound absorption pathways in the product are richer and more rationally distributed, thus improving the sound absorption and noise reduction effects of the product.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. An ABS composite material, characterized in that, The components include the following parts by weight: 50-70 parts of SAN resin, 20-30 parts of high-colloidal powder, 20-40 parts of crystalline resin, and 5-15 parts of functional filler; The crystalline resin includes at least one of PET, PBT, PCTG, and PETG; The functional filler includes organic thermally expandable microspheres and ultrafine inorganic particles, with a mass ratio of organic thermally expandable microspheres to ultrafine inorganic particles of 1:(0.4~10). The average particle size of the organic thermally expandable microspheres is ≤35μm; The retained particle size D of the ultrafine inorganic particles v50 ≤1.5μm.

2. The ABS composite material as described in claim 1, characterized in that, The SAN resin has an acrylonitrile content of 20% to 30% and a melt flow rate of 5 to 50 g / 10 min at 220°C and a load of 10 kg.

3. The ABS composite material as described in claim 1, characterized in that, The high-polymer powder is polybutadiene high-polymer powder; the butadiene monomer content in the high-polymer powder is 55-65%.

4. The ABS composite material as described in claim 1, characterized in that, The melting temperature Tm of the crystalline resin is 230℃≤Tm≤250℃.

5. The ABS composite material as described in claim 1, characterized in that, The organic thermally expandable microspheres have an average particle size of 2~25μm and an initial expansion temperature of ≥85℃.

6. The ABS composite material as described in claim 1, characterized in that, The ultrafine inorganic particles include at least one of ultrafine talc, ultrafine alumina, ultrafine magnesium oxide, ultrafine silicon dioxide, and ultrafine titanium dioxide.

7. The method for preparing the ABS composite material according to any one of claims 1 to 6, characterized in that, Includes the following steps: The components are added to a screw extruder for melt extrusion and granulation to obtain the ABS composite material.

8. The use of the ABS composite material as described in any one of claims 1 to 6 in the manufacture of shell parts.

9. A housing component, characterized in that, Includes the ABS composite material described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • PBT / ABS alloy material and method for preparing same

    CN101284932A

  • Thermoplastic resin composition pellets and method for producing same

    CN118159596A